2012
DOI: 10.1016/j.neuroimage.2012.03.060
|View full text |Cite
|
Sign up to set email alerts
|

Being right is its own reward: Load and performance related ventral striatum activation to correct responses during a working memory task in youth

Abstract: The ventral striatum (VS) is a critical brain region for reinforcement learning and motivation. Intrinsically motivated subjects performing challenging cognitive tasks engage reinforcement circuitry including VS even in the absence of external feedback or incentives. However, little is known about how such VS responses develop with age, relate to task performance, and are influenced by task difficulty. Here we used fMRI to examine VS activation to correct and incorrect responses during a standard n-back workin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
122
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(144 citation statements)
references
References 41 publications
19
122
1
Order By: Relevance
“…These findings complement studies where increased activity in reward-related brain regions-the ventral striatum-is observed after unrewarded accurate performance (e.g., Satterthwaite et al, 2012).…”
Section: The Emotive Nature Of Conflict and Control Implementationsupporting
confidence: 83%
“…These findings complement studies where increased activity in reward-related brain regions-the ventral striatum-is observed after unrewarded accurate performance (e.g., Satterthwaite et al, 2012).…”
Section: The Emotive Nature Of Conflict and Control Implementationsupporting
confidence: 83%
“…Interestingly, the authors demonstrated that correct performance on incongruent, relative to congruent, trials led to a significant benefit in reaction times for the evaluation of positive, relative to negative, words. Similarly, the authors predicted and interpreted this finding by suggesting that people find it more positively surprising to solve a difficult than an easy task (for a similar reasoning, see Alessandri, Darcheville, Delevoye-Turrell, & Zentall, 2008;Braem, Verguts, Roggeman, & Notebaert, 2012;Satterthwaite et al, 2012).…”
Section: Discussionmentioning
confidence: 80%
“…Substantially more work is needed to broaden this understanding and to more fully integrate what is known about large-scale social phenomena with the individual level processes that yield these largerscale phenomena. (68,69), scanning larger and larger samples of individuals (6,70,71), using data sharing and open access data (68,(72)(73)(74), consortium models (75)(76)(77), and neuroimaging meta-analysis (78,79). These models emphasize that neuroimaging approaches can be done on a larger scale and across research teams.…”
Section: Integrative Frameworkmentioning
confidence: 99%